2019
DOI: 10.1002/cptc.201900190
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic Pressure‐Controlled Ratiometric Luminescence Responses of a Dibenzo[a,j]phenazine‐Cored Mechanoluminophore

Abstract: Understanding changes in excited state properties under the influence of an external stimulus, such as pressure or temperature, is important in the context of optimizing molecular components for a number of applications including sensors and imaging reagents. Herein, we use UV/Vis absorption, fluorescence and excitation spectroscopies and fluorescence lifetime measurements supported by calculations to probe the effect of hydrostatic pressure on the excited state characteristics of a conformationally-divergent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 91 publications
(27 reference statements)
2
46
0
Order By: Relevance
“…Indeed, we have recently revealed that optical properties, molecular and biomolecular recognition behavior and photo-physical/chemical processes in solutions of various molecular, supramolecular, macromolecular and biomacromolecular systems are precisely regulated by hydrostatic pressure. [53][54][55][56][57][58][59][60][61][62][63] Hence, these trends prompted us to newly investigate an applicable supramolecular recognition system under hydrostatic pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have recently revealed that optical properties, molecular and biomolecular recognition behavior and photo-physical/chemical processes in solutions of various molecular, supramolecular, macromolecular and biomacromolecular systems are precisely regulated by hydrostatic pressure. [53][54][55][56][57][58][59][60][61][62][63] Hence, these trends prompted us to newly investigate an applicable supramolecular recognition system under hydrostatic pressures.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 4, the fluorescence intensities of H gradually decrease with increasing pressure. It is well‐known that fluorescence intensities of common organic fluorophores increase with increasing pressure due to increasing solvent viscosities, [45,59,60] enabling us to rule out the pressure effect on the dansyl branch itself. The d I /d P at 0.1–20 MPa is steeper, rather than the gentler slope at ≥40 MPa, which means that the included fluorescence branch is kicked out to more polar solvent (bulk water) at the early pressurization stage.…”
Section: Resultsmentioning
confidence: 99%
“…The high‐pressure apparatus was used for spectroscopic measurements. The details were reported previously [59–64] . Sapphire windows were employed for UV/vis and fluorescence spectroscopy and lifetime measurements, while birefringence‐free diamond windows were employed for circular dichroism spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Takeda, Penfold, and Fukuhara recently investigated the effect of hydrostatic pressure on the photophysical properties of 9e in solution, where the fluctuation of molecular conformations would be more sensitive toward the materials environments. 32 In contrast to the solid states, 9e in toluene shows 3 distinct CT emissions derived from the 3 different conformers (eq-eq, ax-eq, and ax-ax types) (Fig. 12a).…”
Section: Dbphz-cored D-a-d Triads As Beyond Single Photo-functionalitymentioning
confidence: 98%